Role of the Media in Providing Constitutional Law and Order - YASTREBOVA, Anna; SKURATOV, Yurij; SKURATOV, Yurij; DZHAVAKHYAN, Roman; DZHAVAKHYAN, Roman (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article aims to elaborate doctrinal positions disclosing features of interaction between public authorities and civil society in the resolution of the most complicated tasks of the present, including by ensuring constitutional law and order and improving statutory and legal foundations of their interaction. One of the leading approaches to the study of this problem is the dialectic interaction of state legal institutions and civil society institutions. In the article, the authors have analyzed provisions of international acts and Russian national laws governing the interaction between the state and civil society (the mass media), including during armed conflicts. and measures aimed to ensure constitutional law and order. RESUMEN El artículo tiene como objetivo elaborar posturas doctrinales que revelen características de interacción entre las autoridades públicas y la sociedad civil en la resolución de las tareas más complicadas del presente, incluso asegurando la ley y el orden constitucionales y mejorando los fundamentos legales de su interacción. Uno de los enfoques principales para el estudio de este problema es la interacción dialéctica de las instituciones legales estatales y las instituciones de la sociedad civil. En el artículo, los autores analizaron las disposiciones de los actos internacionales y las leyes nacionales rusas que rigen la interacción entre el estado y la sociedad civil (los medios de comunicación), incluso durante los conflictos armados. y medidas destinadas a garantizar el orden y leyes constitucionales.